Change of pathology request forms can reduce unwanted requests and tests. Issue 8 (27th July 2005) - Bailey, J; Jennings, A; Parapia, L
Abstract : Background: Developments in clinical and laboratory medical practice have resulted in a large increase in laboratory workload, with considerable financial implications. It has been shown that the design of laboratory request cards can influence patterns of test ordering and possibly reduce inappropriate requests. Aims/Methods: To redesign pathology request cards with a view to reducing inappropriate test requesting. Results: A redesign of the request cards used by general practitioners in the Bradford area led to a significant reduction in the ordering of specific investigations. Conclusions: The redesigning of pathology request cards can have a beneficial effect on test requesting.